Process optimization of hydrocolloid production from seaweeds - Jaswir, Irwandi; Kodin, Mohd Razi; Jamal, Parveen (IIUM Press, 2011)
This study was undertaken to find the optimum conditions for the extraction of hydrocolloids from seaweed of species Gracilarza changii. Recent trend of seaweed industry in producing hydrocolloids component shows a decline because of the high cost of production. Hence, an optimum parameter is now crucial to maximize the yield and the quality, at the same time minimize loss. Furthermore, the concern about the halal food among Muslim give advantage to hydrocolloids that have similar properties to gelatin, make it a suitable substitutes in food industry. Hydrocolloids from seaweed consist of three components, which are agar, carrageenan and alginates. The initial screening test shows that agar is the most abundance hydrocolloids with 13.70 mg/g yield. The optimal conditions for maximum yield were found at 5% NaOH concentration with 0.5 hours treatment time and 3 hours extraction time. Maximum gel strength was obtained for seaweed treated with 8% NaOH solution with 0.5 hours treatment time and 1 hour extraction time with 313.6 gcm-2 gel strength.